The use of IT and OER to support remote sustainable work in Europeans Green Economy - Beutner, Marc; Schneider, Jennifer Nicole (International Conference on Industry Sciences and Computer Science Innovation)

Weiterbildung des Weiterbildungspersonals – Vorwiegend eine Aufgabe des Lernens am Arbeitsplatz - Schwede, Jana; Harteis, Christian (Nachhaltigkeitsorientierte Weiterbildungsdidaktik: Die doppelte Multiplikatorenqualifizierung)

Auswirkungen einer Online-Intervention (Mindset, Lerntechniken) auf den Studieneinstieg - Diederich, Malte; Spatz, Verena; Bauer, Anna Brigitte (Phydid B, Didaktik der Physik, Beiträge zur DPG-Frühjahrstagung (2022))

Towards a Data-Driven Product Management – Concepts, Advantages, and Future Research - Fichtler, Timm; Grigoryan, Khoren; Koldewey, Christian; Dumitrescu, Roman (2023 IEEE International Conference on Technology Management, Operations and Decisions (ICTMOD))
Megatrends, such as digitization or sustainability, are confronting the product management of manufacturing companies with a variety of challenges regarding the design of future products, but also the management of the actual products. To successfully position their products in the market, product managers need to gather and analyze comprehensive information about customers, developments in the products’ environment, product usage, and more. The digitization of all aspects of life is making data on these topics increasingly available – via social media, documents, or the internet of things from the products themselves. The systematic collection and analysis of these data enable the exploitation of new potentials for the adaption of existing products and the creation of the products of tomorrow. However, there are still no insights into the main concepts and cause-effect relationships in exploiting data-driven approaches for product management. Therefore, this paper aims to identify the main concepts and advantages of data-driven product management. To answer the corresponding research questions a comprehensive systematic literature review is conducted. From its results, a detailed description of the main concepts of data-driven product management is derived. Furthermore, a taxonomy for the advantages of data-driven product management is presented. The main concepts and the taxonomy allow for a deeper understanding of the topic while highlighting necessary future actions and research needs.
Keywords: Product Lifecyle Management (PLM); Data Analytics; Data-driven Design; Engineering Management; Lifecycle Data

Academic self-concepts of pre-service technology teachers for vocational education in Germany according to the TPACK- Model - Vernholz, Mats (Living and Leading in the Next Era: Connecting Teaching, Research, Citizenship and Equity)

CFD-Untersuchungen der Fluiddynamik und des Wärmetransports an rauen Oberflächen - Hollenhorst, Viola; Kenig, Eugeny Y.

Modellierung der Reaktivabsorption in regellosen Schüttungen und modellbasierte Optimierung von Füllkörpern mit dem Ansatz der hydrodynamischen Analogien - Salten, Alexander Heinrich Johannes
Füllkörper spielen in industriellen Trennprozessen eine wichtige Rolle bspw. bei der Reinigung industrieller Abgase durch Absorption. Die Trennleistung von Füllkörperkolonnen wird üblicherweise mittels vereinfachter Stufenmodelle ermittelt, deren Modellparameter experimentell bestimmt werden müssen. Dies stellt eine große Schwäche von Stufenmodellen dar, da diese Parameterim Allgemeinen nicht auf verschiedene Stoffsysteme und Füllkörpertypen übertragbar sind.In dieser Arbeit wird ein Modell, basierend auf dem hydrodynamischen Analogieansatz, zur Beschreibung von Absorptionsvorgängen in Füllkörperkolonnen vorgestellt. Dabei ist die Geometrie der festen Phase direkt abhängig von der Füllkörpergeometrie und der Stochastik der Schüttung. Die tatsächlichen Strömungsverhältnisse in Füllkörperkolonnen werden erfasst und durch eine Kombination vereinfachter charakteristischer Strömungsformen reproduziert. Dies erlaubt die Verwendung rigoroser Transportgleichung. Dadurch enthält das Modell weniger experimentell zu ermittelnde Parameter und ist damit unabhängiger von Experimenten als vereinfachte Stufenmodelle. Das Modell wurde gegen experimentelle Daten zur CO2-Absorption in wässrige Natronlauge validiert. Mit dem entwickelten Modell wurde anschließend eine Parameterstudie durchgeführt, die der Unterstützung der Entwicklung neuer Füllkörpergeometrien dient. Dazu wurde eine Simulationsstudie durchgeführt, die den Einfluss der Füllkörpergeometrie auf die Trennleistung untersucht.

Einseitiges Widerstandselementschweißen für die stahlintensive Mischbauweise - Haak, Viktor; Meschut, Gerson; Epperlein, Maike; Schiebahn, Alexander; Reisgen, Uwe (25. DVS-Sondertagung Widerstandsschweißen)

Optimal scheduling of a large-scale power-to-ammonia process: Effects of parameter optimization on the indirect demand response potential - Hochhaus, Thorben; Bruns, Bastian; Grünewald, Marcus; Riese, Julia (Computers & Chemical Engineering)
Keywords: Computer Science Applications; General Chemical Engineering

Demand Side Management Implementation in Downstream Digestate Treatment of a Biomethane Biorefinery - Röder, Lilli Sophia; Gröngröft, Arne; Grünewald, Marcus; Riese, Julia (Chemical Engineering Transactions)

Decision support tool to determine the suitability of demand side management implementation in continuously operated processes – A biorefinery case study - Röder, Lilli; Etzold, Hendrik; Gröngröft, Arne; Grünewald, Marcus; Riese, Julia (Biofuels, Bioproducts and Biorefining)
Abstract The time‐dependent adjustment of a system's power demand simultaneously with current power generation is commonly referred to as demand side management (DSM). DSM strategies are based on the flexibility to purchase electricity at times when prices are low, which can result in monetary benefits. One option to increase the flexibility of continuously operated processes is to oversize them. From an economic point of view, this leads to an increased investment. DSM only serves an economic purpose if the monetary benefits exceed this increase in capital costs. The main goal of this contribution is to develop a decision support tool to help evaluate unit operations regarding their feasibility for DSM implementation. In a case study, the decision support tool was applied to show its functionality on a biomethane production plant. The results show that with the help of the decision support tool, evaluating unit operations concerning their economic DSM potential is possible.
Keywords: Renewable Energy; Sustainability and the Environment; Bioengineering

Intersektionalität und erzählte Welten – Einführung - Abrego, Verónica; Henke, Ina; Kißling, Magdalena; Lammer, Christina; Leuker, Maria-Th. (Intersektionalität und erzählte Welten. Fachwissenschaftliche und fachdidaktische Perspektiven auf Literatur und Medien)

Het verschil tussen strips en graphic novels (in Vlaanderen) - Lammer, Christina

Power-to-hydrogen and hydrogen-to-X energy systems for the industry of the future in Europe - Genovese, Matteo; Schlüter, Alexander; Scionti, Eugenio; Piraino, Francesco; Corigliano, Orlando; Fragiacomo, Petronilla (International Journal of Hydrogen Energy)
Keywords: Hydrogen economy; Green hydrogen; Power-to-X; Hydrogen-to-X; Sector coupling

Pre-equilibrium photons from the early stages of heavy-ion collisions - Oscar Garcia-Montero, Oscar Garcia-Montero; Mazeliauskas, Aleksas; Plaschke, Philip; Schlichting, Sören (arXiv:2308.09747)
We use QCD kinetic theory to compute photon production in the chemically equilibrating Quark-Gluon Plasma created in the early stages of high-energy heavy-ion collisions. We do a detailed comparison of pre-equilibrium photon rates to the thermal photon production. We show that the photon spectrum radiated from a hydrodynamic attractor evolution satisfies a simple scaling form in terms of the specific shear viscosity $η/s$ and entropy density $dS/dζ \sim {\scriptstyle \left(Tτ^{1/3}\right)^{3/2}}_∞$. We confirm the analytical predictions with numerical kinetic theory simulations. We use the extracted scaling function to compute the pre-equilibrium photon contribution in $\sqrt{s_{NN}}=2.76\,\text{TeV}$ 0-20% PbPb collisions. We demonstrate that our matching procedure allows for a smooth switching from pre-equilibrium kinetic to thermal hydrodynamic photon production. Finally, our publicly available implementation can be straightforwardly added to existing heavy ion models.

Open Educational Resources in der beruflichen Bildungslandschaft - Schneider, Jennifer Nicole

Experimental Study of an Internally Channeled Tube Heat Exchanger under Turbulent Flow Conditions - Al-Lami, Abbas Jarullah Sangoor; Kenig, Eugeny (International Journal of Heat and Mass Transfer)

Der Wirtschaft auch in der Krise das Atmen erlauben, Pandemie und Ökonomie – Interview mit Steuerexpertin Caren Sureth-Sloane - Unterstell, Rembert

Allowing the Economy to Breathe Even During the Crisis – Interview with Tax Expert Caren Sureth-Sloane - Unterstell, Rembert

Numerical analysis of failure modeling in clinching process chain simulation - Bielak, Christian Roman; Böhnke, Max; Friedlein, Johannes; Bobbert, Mathias; Mergheim, Julia; Steinmann, Paul; Meschut, Gerson (Materials Research Proceedings)
Abstract. The application of the mechanical joining process clinching allows the assembly of different sheet metal materials with a wide range of material thickness configurations, which is of interest for lightweight multi-material structures. In order to be able to predict the clinched joint properties as a function of the individual manufacturing steps, current studies focus on numerical modeling of the entire clinching process chain. It is essential to be able to take into account the influence of the joining process-induced damage on the load-bearing capacity of the joint during the loading phase. This study presents a numerical damage accumulation in the clinching process based on an implemented Hosford-Coulomb failure model using a 3D clinching process model applied on the aluminum alloy EN AW-6014 in temper T4. A correspondence of the experimentally determined failure location with the element of the highest numerically determined damage accumulation is shown. Moreover, the experimentally determined failure behavior is predicted to be in agreement in the numerical loading simulation with transferred pre-damage from the process simulation.

A calibration method for failure modeling in clinching process simulations - Böhnke, Max; Bielak, Christian Roman; Friedlein, Johannes; Bobbert, Mathias; Mergheim, Julia; Steinmann, Paul; Meschut, Gerson (Materials Research Proceedings)
Abstract. In the numerical simulation of mechanical joining technologies such as clinching, the material modeling of the joining parts is of major importance. This includes modeling the damage and failure behavior of the materials in accordance with varying occurring stress states. This paper presents a calibration method of three different fracture models. The calibration of the models is done by use of experimental data from a modified punch test, tensile test and bulge test in order to map the occurring stress states from clinching processes and to precisely model the resulting failure behavior. Experimental investigations were carried out for an aluminum alloy EN AW-6014 in temper T4 and compared with the simulative results generated in LS-DYNA. The comparison of force-displacement curves and failure initiation shows that the Hosford–Coulomb model predicts the failure behavior for the material used and the tests applied with the best accuracy.

Experimental and Numerical Investigation of Clinched Joints Under Shear Tensile Loading at High Strain Rates - Böhnke, Max; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (Lecture Notes in Mechanical Engineering)

Influence of plastic orthotropy on clinching of sheet metal - Friedlein, Johannes; Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Mergheim, Julia; Steinmann, Paul; Meschut, Gerson (Materials Research Proceedings)

Karneval und OWL - Breckner, Anne

Auszeit - Breckner, Anne

Was brauchst du? Engagement für die Mitmenschen in Christentum und Islam. Interreligiöse Unterrichtsreihe im Themenheft Diakonie - Breckner, Anne; Kamcili-Yildiz, Naciye (Religion 5-10)

Economic Integration of a High-Temperature Heat Pump with Flexible Part-load Operation - Knorr, Lukas; Schlosser, Florian; Meschede, Henning

Untersuchung des Reibungs- und Deformationsverhaltens von schnelllaufenden Bremsen - Rauhaus, Johann; Schadomsky, Magnus; Magyar, Balázs; Zimmer, Detmar (Tagungsband der 64. Tribologie-Fachtagung)

Determination and Compensation of the Shrinkage Behavior of Cylindrical Elements in the FDM Process - Koers, Thorsten; Magyar, Balázs (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium 2023)
Fused Deposition Modeling (FDM) is an additive manufacturing process to produce complex thermoplastic geometries layer by layer. The filament is melted in a nozzle, iteratively deposited, and then cools down. Due to the solidification process, the deposited filament strands deviate from their intended position due to shrinkage, resulting in significant geometric deviations in the final part. In terms of dimensional accuracy, there is a need for optimization, especially for local curved geometries in relation to the global part with higher nominal dimensions. The aim of this study is to investigate the size and shape deviations for cylindrical FDM elements and to compensate the expected deformations by using an in-house software with adaptive scaling factors in the x-y plane. Previous studies mainly focus on simple, non-curved objects, this study also considers the influence of curvature and global as well as local deviations on the final part.

Depiction of support structures in technical drawings - Lammers, Stefan; Koers, Thorsten; Magyar, Balázs; Zimmer, Detmar; Lieneke, Tobias (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium 2023)
To ensure uniform documentation of support structure information, a concept is presented that enables a standardized depiction of support structures in technical drawings based on ISO 128-3. To this end, requirements for a uniform depiction are defined and a procedure for drawing entry is presented. The drawing entry should contain all production-relevant support structure information. The standardized documentation of support structure information in technical drawings is intended to ensure a simple, clear and safe exchange of information between business units or different companies along the value chain. As a result a possible drawing entry of support structures was developed. To distinguish between different support structure types, a standardized depiction of geometrical information in a specification field is shown. The specification field gives a detailed description of the support structure type, the geometry as well as the connection to the part and the building platform. Also uncommon support types like lattice structures or CAD based support structures can be implemented. To ensure the usability the depictio is editable and extendable.

Übergang Schule-Beruf als Chancenverbesserungssystem – Zur Gestaltung von Lebensräumen und Entwicklung von Praktiken für den Übergang - Kremer, H.-Hugo; Otto, Franziska (bwp@ Berufs- und Wirtschaftspädagogik – online)
Sich wandelnde Bedingungen auf dem Ausbildungsmarkt, die daraus resultierenden veränderten Kompetenz- und Qualifikationsanforderungen sowie Anforderungen an eine lebensbegleitende berufliche Orientierung treffen insb. als (ausbildungs-)benachteiligt gekennzeichnete Jugendliche am Übergang Schule-Beruf. Jene Jugendliche münden in Maßnahmen des Übergangssystems wie die Ausbildungsvorbereitung (AV), wobei die konkreten Auswirkungen dieser Transformationsprozesse für diese Zielgruppe weitgehend unklar bleiben. In unserem Beitrag greifen wir die Überlegungen der Arbeitsgruppe 9+1 zum Übergangssystem verstanden als Chancenverbesserungssystem auf und diskutieren, was hierunter verstanden werden kann. Schließlich führen wir konkrete Anforderungen an das Chancenverbesserungssystem mit den Handlungsmöglichkeiten der Jugendlichen zusammen. Grundlegend verfolgen wir dabei nicht die Perspektive einer Anpassung der Jugendlichen an die Arbeitswelt, sondern fragen vielmehr danach, was Bildung leisten muss. Hierfür nehmen wir über qualitative Fallstudien die Perspektive der Jugendlichen sowie die Sichtweise des Bildungspersonals auf. In diesem Rahmen führen wir eine anforderungs- und subjektorientierte Perspektive zusammen und diskutieren u. a. anhand von Perspektiven auf das System, die curriculare Ebene, die Haltung der Bildungsakteur*innen, etc., was mit einer Gestaltung des Übergangssystems als Chancenverbesserungssystem konkret verbunden wäre.
Keywords: Übergangssystem; Selbstinszenierung; Chancenverbesserung; Subjektorientierung; Übergang Schule-Ausbildung

Modeling Highlighting of Metaphors in Multitask Contrastive Learning Paradigms - Sengupta, Meghdut; Alshomary, Milad; Scharlau, Ingrid; Wachsmuth, Henning (Findings of the Association for Computational Linguistics: EMNLP 2023)

Selektives Lasersintern mit glasverstärkten Kunstsoff-Dry-Blends Analyse von Verarbeitbarketi und Bauteileigenschaften im Vergleich zu partikelgefüllten Kunststoffpulvern - Tschöpe, Jan-Cedric Philipp Balthasar

Open Data in musikphilologischen Projekten: Herausforderungen, Strategien, Potenziale - Kepper, Johannes; Münzmay, Andreas (DHd2023: Open Humanities, Open Culture)

Back to the Roots: Predicting the Source Domain of Metaphors using Contrastive Learning - Sengupta, Meghdut; Alshomary, Milad; Wachsmuth, Henning (Proceedings of the 3rd Workshop on Figurative Language Processing (FLP))

Investigating the Viability of Existing Exploratory Landscape Analysis Features for Mixed-Integer Problems - Prager, Raphael Patrick; Trautmann, Heike (Companion Proceedings of the Conference on Genetic and Evolutionary Computation, GECCO 2023, Companion Volume, Lisbon, Portugal, July 15-19, 2023)

A Bouquet of Encounters With Faux Flora Across Time – A Visual Essay. - Kraft, Kerstin

Influences on the Flow Behavior of Highly Viscous Thermal Interface Materials in the Joining Process - Gilich, Julian; Meschut, Gerson; Wiebicke, Felix; Gröger, Benjamin; Kuhtz, Moritz; Koch, Ilja; Gude, Maik (14th European Adhesion Conference (EURADH) & 7th World Congress on Adhesion and Related Phenomena (WCARP))

Innovation und neue Stabilitäten durch Krisenzeiten — zur Wandlungs- und Transformationsfähigkeit der beruflichen Integrationsförderung - Schemmer, Susanne Jutta (Arbeitsmarktgeförderte berufliche Integration, berufsbildung, 77 (3). Bielefeld: wbv Publikation, 2-4.)

Quo Vadis CO2 Activation: Catalytic Reduction of CO2 to Methanol Using Aluminum and Gallium/Carbon‐based Ambiphiles - Krämer, Felix; Paradies, Jan; Fernández, Israel; Breher, Frank (Chemistry – A European Journal)
Abstract We report on so‐called “hidden FLPs” (FLP: frustrated Lewis pair) consisting of a phosphorus ylide featuring a group 13 fragment in the ortho position of a phenyl ring scaffold to form five‐membered ring structures. Although the formation of the Lewis acid/base adducts was observed in the solid state, most of the title compounds readily react with carbon dioxide to provide stable insertion products. Strikingly, 0.3–3.0 mol% of the reported aluminum and gallium/carbon‐based ambiphiles catalyze the reduction of CO 2 to methanol with satisfactory high selectivity and yields using pinacol borane as stoichiometric reduction equivalent. Comprehensive computational studies provided valuable mechanistic insights and shed more light on activity differences.
Keywords: General Chemistry; Catalysis; Organic Chemistry

Mashood A. Baderin, Islamic Law. A Very Short Introduction - Nassery, Idris

Digitalisiertes Arbeiten in gastgewerblichen Berufen – Umsetzung in der Hochschullehre - Härtel, Sandra; Klatt, Christiane; Meyer, Anja (HiBiFo – Haushalt in Bildung & Forschung)
In einem Seminar für angehende berufsbildende Lehrkräfte der beruflichen Fachrichtung Ernährung und Hauswirtschaft an der Technischen Universität Dresden wurde mittels digitaler Tools ein Property-Management-System dargestellt. Ziel ist es, Geschäfts- und Arbeitsprozesse in der Hotellerie sowie digitale Medien und ihre Einsatzmöglichkeiten innerhalb von Lehrveranstaltungen abzubilden.
Keywords: General Medicine

Influence of thermo-mechanical joining process on the microstructure of a hypoeutectic aluminium cast alloy - Borgert, Thomas; Neuser, Moritz; Wiens, Eugen; Grydin, Olexandr; Homberg, Werner; Schaper, Mirko (Materials Research Proceedings)
Abstract. Requirements of multi-material construction involve adjustments to standard joining techniques. Especially the growing importance of integral cast components poses additional engineering challenges for the industry. One approach to achieve these goals are adaptable joining elements formed by friction spinning. This approach uses friction-induced heat to form customisable joining elements to join sheets for different boundary conditions, even for brittle cast materials. It is possible to react immediately to adapt to the joining process inline and reduce the amount of different joining elements. As the joining partner serve casting plates of the aluminium casting alloy EN AC–AlSi9, which is processed in the sand casting. Joining hypoeutectic AlSi alloys constitutes a challenge because the brittle character of these cause cracks in the joint during conventional mechanical joining. Furthermore, the friction-induced heat of the novel joining process causes a finer microstructure in the hypoeutectic AlSi9 casting alloy. In particular, the eutectic Si is more fine-grained, resulting in higher joint ductility. This study indicates the joining suitability of a hypoeutectic aluminium casting alloy in combination with adaptive manufactured additional joining elements. Here, various mechanical and microstructural investigations validate the influence of the thermomechanical joining technique. In conclusion, the potential of this joining process is presented regarding the joinability of cast aluminium components.

Mechanical and Microstructure Characterisation of the Hypoeutectic Cast Aluminium Alloy AlSi10Mg Manufactured by the Twin-Roll Casting Process - Neuser, Moritz; Schaper, Mirko; Grydin, Olexandr (Journal of Manufacturing and Materials Processing)
Multi-material designs (MMD) are more frequently used in the automotive industry. Hereby, the combination of different materials, metal sheets, or cast components, is mechanically joined, often by forming joining processes. The cast components mostly used are high-strength, age-hardenable aluminium alloys of the Al–Si system. Here, the low ductility of the AlSi alloys constitutes a challenge because their brittle nature causes cracks during the joining process. However, by using suitable solidification conditions, it is possible to achieve a microstructure with improved mechanical and joining properties. For this study, we used the twin-roll casting process (TRC) with water-cooled rollers to manufacture the hypoeutectic AlSi10Mg for the first time. Hereby, high solidification rates are realisable, which introduces a microstructure that is about four times finer than in the sand casting process. In particular, it is shown that a fine microstructure close to the modification with Na or Sr is achieved by the high solidification rate in the TRC process without using these elements. Based on this, the mechanical properties increase, and especially the ductility is enhanced. Subsequent joining investigations validate the positive influence of a high solidification rate since cracks in joints can be avoided. Finally, a microstructure-property-joint suitability correlation is presented.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Thermomechanical Joining of Hypoeutectic Aluminium Cast Plates - Borgert, Thomas; Neuser, Moritz; Hoyer, Kay-Peter; Homberg, Werner; Schaper, Mirko (Journal of Manufacturing and Materials Processing)
Consistent lightweight construction in the area of vehicle manufacturing requires the increased use of multi-material combinations. This, in turn, requires an adaptation of standard joining techniques. In multi-material combinations, the importance of integral cast components, in particular, is increasing and poses additional technical challenges for the industry. One approach to solve these challenges is adaptable joining elements manufactured by a thermomechanical forming process. By applying an incremental and thermomechanical joining process, it is possible to react immediately and adapt the joining process inline to reduce the number of different joining elements. In the investigation described in this publication, cast plates made of the cast aluminium alloy EN AC-AlSi9 serve as joining partners, which are processed by sand casting. The joining process of hypoeutectic AlSi alloys is challenging as their brittle character leads to cracks in the joint during conventional mechanical joining. To solve this, the frictional heat of the novel joining process applied can provide a finer microstructure in the hypoeutectic AlSi9 cast alloy. In detail, its Si is finer-grained, resulting in higher ductility of the joint. This study reveals the thermomechanical joining suitability of a hypoeutectic cast aluminium alloy in combination with adaptively manufactured auxiliary joining elements.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Influence of Shell Material on the Microstructure and Mechanical Properties of Twin-Roll Cast Al-Si-Mg Alloy - Grydin, Olexandr; Neuser, Moritz; Schaper, Mirko (Conference: ICTP 2023: Proceedings of the 14th International Conference on the Technology of Plasticity - Current Trends in the Technology of PlasticityAt: Cannes (France))

Using Reinforcement Learning for Per-Instance Algorithm Configuration on the TSP - Seiler, Moritz Vinzent; Rook, Jeroen; Heins, Jonathan; Preuß, Oliver Ludger; Bossek, Jakob; Trautmann, Heike (2023 IEEE Symposium Series on Computational Intelligence (SSCI))
Automated Algorithm Configuration (AAC) usually takes a global perspective: it identifies a parameter configuration for an (optimization) algorithm that maximizes a performance metric over a set of instances. However, the optimal choice of parameters strongly depends on the instance at hand and should thus be calculated on a per-instance basis. We explore the potential of Per-Instance Algorithm Configuration (PIAC) by using Reinforcement Learning (RL). To this end, we propose a novel PIAC approach that is based on deep neural networks. We apply it to predict configurations for the Lin– Kernighan heuristic (LKH) for the Traveling Salesperson Problem (TSP) individually for every single instance. To train our PIAC approach, we create a large set of 100000 TSP instances with 2000 nodes each — currently the largest benchmark set to the best of our knowledge. We compare our approach to the state-of-the-art AAC method Sequential Model-based Algorithm Configuration (SMAC). The results show that our PIAC approach outperforms this baseline on both the newly created instance set and established instance sets.

Die Totenmaske als Medium der kleinen Form. Zur Mehrdeutigkeit von Ahnenkult und Historie im frühen 20. und 21. Jahrhundert - Öhlschläger, Claudia (Scientia Poetica)

Anthropologie - strittig zwischen Christentum und Islam? - Tatari, Muna; Ströbele, Christian (Herausforderung Mensch)

Kirche und Musiktheater. Ein ambivalentes Verhältnis in Schlaglichtern - Adler, Luise; Tumat, Antje (Loccumer Pelikan. Religionspädagogisches Magazin für Schule und Gemeinde des Religionspädagogischen Instituts Loccum)

Grundlagen der Medienökonomie: Medien, Wirtschaft und Gesellschaft. - Fuchs, Christian

The Identification of a New Liquid Metal Embrittlement (LME) Type in Resistance Spot Welding of Advanced High-Strength Steels on Reduced Flange Widths - Yang, Keke; Meschut, Gerson; Seitz, Georg; Biegler, Max; Rethmeier, Michael (Metals (Special Issue Embrittlement Phenomena in Steel Metallurgy))

Auslegungsmethode zum Kleben höchstfester Stahlwerkstoffe im Landmaschinenbau - Göddecke, Johannes; Göhrs, Tim; Meschut, Gerson; Große Gehling, Manfred (Stahlbau)
Abstract In Konstruktionen des Landmaschinenbaus aus dickeren Blechen (ca. 3–10 mm) findet die Klebtechnik bislang nur wenig Anwendung, obwohl sie in anderen Einsatzgebieten bereits ein etabliertes Fügeverfahren darstellt und viele Vorteile gegenüber anderen Fügeverfahren bietet, da es bisher an Regelwerken bei der Auslegung derartiger Verbindungen fehlt. Ein wesentliches Kriterium bei der Auslegung von Verbindungen im Landmaschinenbau ist die Ermüdungsfestigkeit aufgrund der langen Nutzungsphase der Produkte und der in der Landtechnik vorherrschenden Belastungscharakteristika. Geklebte Verbindungen weisen ein hervorragendes Verhalten bei zyklischer Belastung auf. Die steigenden Anforderungen im Hinblick auf Ressourceneffizienz und Leichtbau führen zu einem Umdenken, da durch den vermehrten Einsatz höherfester Stahlwerkstoffe in Kombination mit der Klebtechnik dieses als umsetzbar erscheint. Ziel ist die Entwicklung einer Methode zur Auslegung geklebter Verbindungen in Konstruktionen mit höherfesten Stahlwerkstoffen in Anlehnung an die FKM‐Richtlinie. Die betriebsrelevanten Beanspruchungen der Landtechnik werden analysiert und an speziellen Probekörpern untersucht. Dabei werden sowohl die mechanischen, thermischen und medialen Einflussfaktoren als auch der Einfluss der Klebfugengeometrie und von Betriebslastenkollektiven untersucht. Die Erkenntnisse werden in einer KMU‐relevanten Vorgehensweise zur Ermittlung von Abminderungsfaktoren zusammengefasst, wodurch die Auslegung der Bauteilfestigkeit sowohl statisch als auch dynamisch möglich ist.
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials; Building and Construction; Civil and Structural Engineering

Rechnergestützte Versagensanalyse geklebter Verbindungen - Chudalla, Nick; Meschut, Gerson; Teutenberg, Dominik; Schneider, Miriam; Smart, Dominic (adhäsion KLEBEN & DICHTEN)

Rheologische Charakterisierung von Frischbeton : Entwicklung eines adaptiven Rheometers und Untersuchung wandgleitunterdrückender Messgeometrien - Josch, Sebastian

Sprachbildung in technischen und pflegerischen Fächern der beruflichen Bildung. Bildung und Beruf. - Heil, Rebekka (Zeitschrift des Bundesverbandes der Lehrkräfte für Berufsbildung e.V.)

ProDaZ Online-Tool Technik - Heil, Rebekka; Prange, Sarah-Christin

ProDaZ Online-Tool Pflege. - Heil, Rebekka

Numerical Computation of Capillary Bridges between Directly Resolved Rough Interfaces - Gräßer, Melanie

Der Einfluss verschiedener Luftfilter auf die Geräuschemissionen von Personenkraftwagen - Peper, Frederik

Qualifizierung des kyrogenen Mahlens zur Herstellung von gefüllten Kunststoffpulvern für das Lasersinterverfahren (Studienarbeit) - Wiebe, Robert

Polystyrol Nanopartikel asl alternative Fließhilfsmittel für SLS Materialien (Studienarbeit) - Aissani, Soufiane

Der Einfluss verschiedener Partikelgrößenfraktionen eines PA12 Pulvers auf den Lasersinterprozess und auf die resultierenden Bauteileigenschaften - Middelmann, Steffen

Untersuchung und Modellierung der Materialeigenschaften von lasergesintertem Polyamid 11 Pulver mit eincompoundierten Carbonfasern - Schröder, Dominik

Schmelze-Temperatur-Messung im Lasersinter-Prozess und Korrelation zu temperaturabhängigen Schmelzviskositäten - Baaske, Benno

Numerical Investigations on the Flow Field and the Transfer Function of a Centrifugal-DMA - Gröne, Sebastian

Konstruktion einer Vorrichtung zur Probenherstellung für das Sentmanat-Dehnrheometer - Otto, Moritz

Entwicklung einer Datenbank hergestellter Nanomaterialien mittel Gasphasensynthese (Studienarbeit) - Reimer, Jens

Materialqualifizierung und Nachhaltigkeitsanalyse eines biobasierten Polyamid 11-Pulvers für das selektive Lasersintern - Schulenkorf, Steffen

Entwicklung eines Verfahrens zur Probeentnahme aus einem Pulverkuchen im SLS-Prozess - Bürckner, Lorena Marie

Studie zum Auftragsverhalten von SLS-Pulvern in Abhängigkeit ihrer Fließfähigkeit - Engemann, Julian

Untersuchungen zum Einfluss der Pulverkonzentration auf den dynamischenmechanischen Partikelverrundungsprozess (Studienarbeit) - Hormatallah, Mouhssine; Ponusamy, SathishKumar

Leistungsbedarf beim dynamisch - mechanischen Partikelverrundungsprozess (Studienarbeit) - Tappe, Daniel; Ponusamy, SathishKumar

Polymorphic uncertainty in constitutive modeling of polymer composites at different scales - Penner, Eduard

Manufacturing-Morphology-Property Relationships for Rotating Shaft Sealing Systems - Thielen, Stefan; Antonyuk, Sergiy; Aurich, Jan C.; Beck, Tilmann; Hasse, Hans; Kopnarski, Michael; Magyar, Balázs; Sauer, Bernd; Smaga, Marek (Component Surfaces)

Measurement, Modelling, and Appli cation of Lubricant Properties at Extreme Pressures - Wingertszahn, Patrick; Schmitt, Sebastian; Thielen, Stefan; Oehler, Manuel; Magyar, Balázs; Koch, Oliver; Hasse, Hans; Stephan, Simon (Tribologie und Schmierungstechnik)
Lubricants play a central role in many technical applications, e.g. in bearings and gears as well as in machining processes. In such applications, lubricants are exposed to extreme conditions in the contact area. In lubrication gaps, the pressure can reach values up to 5 GPa. The thermophysical properties of lubricants, and in particular the viscosity, at such extreme conditions have an important influence on the friction and wear behavior of a tribosystem. Accordingly, reliable lubricant property models are a prerequisite for accurate tribological simulations, e.g. elastohydrodynamic lubrication (EHL) simulations. Presently, the vast majority of experimental thermophysical property data are only available up to 1 GPa. Thus, reliable and robust models with strong extrapolation capabilities to higher pressure are required. In this work, viscosity measurements of squalane in a temperature range be tween 20 °C and 100 °C and pressures up to 1 GPa were carried out. Based on that data, a physical model for the viscosity was developed. The model is built by combining a molecular-based equation of state with the so-called entropy scaling approach. Finally, we demonstrate how this fluid property model can be favorably integrated in an EHL simulation by an application programming interface (API). The novel hybrid modeling approach is promising for future applications.
Keywords: Surfaces; Coatings and Films; Surfaces and Interfaces; Mechanical Engineering; Mechanics of Materials

Evaluation of Usability Criteria Addressed by Static Analysis Tools on a Large Scale - Nachtigall, Marcus; Schlichtig, Michael; Bodden, Eric (Software Engineering 2023)
Static analysis tools support developers in detecting potential coding issues, such as bugs or vulnerabilities. Research emphasizes technical challenges of such tools but also mentions severe usability shortcomings. These shortcomings hinder the adoption of static analysis tools, and user dissatisfaction may even lead to tool abandonment. To comprehensively assess the state of the art, we present the first systematic usability evaluation of a wide range of static analysis tools. We derived a set of 36 relevant criteria from the literature and used them to evaluate a total of 46 static analysis tools complying with our inclusion and exclusion criteria - a representative set of mainly non-proprietary tools. The evaluation against the usability criteria in a multiple-raters approach shows that two thirds of the considered tools off er poor warning messages, while about three-quarters provide hardly any fix support. Furthermore, the integration of user knowledge is strongly neglected, which could be used for instance, to improve handling of false positives. Finally, issues regarding workflow integration and specialized user interfaces are revealed. These findings should prove useful in guiding and focusing further research and development in user experience for static code analyses.
Keywords: Automated static analysis; Software usability

Introducing FUM: A Framework for API Usage Constraint and Misuse Classification - Schlichtig, Michael; Sassalla, Steffen; Narasimhan, Krishna; Bodden, Eric (Software Engineering 2023)
Application Programming Interfaces (APIs) are the primary mechanism developers use to obtain access to third-party algorithms and services. Unfortunately, APIs can be misused, which can have catastrophic consequences, especially if the APIs provide security-critical functionalities like cryptography. Understanding what API misuses are, and how they are caused, is important to prevent them, eg, with API misuse detectors. However, definitions for API misuses and related terms in literature vary. This paper presents a systematic literature review to clarify these terms and introduces FUM, a novel Framework for API Usage constraint and Misuse classification. The literature review revealed that API misuses are violations of API usage constraints. To address this, we provide unified definitions and use them to derive FUM. To assess the extent to which FUM aids in determining and guiding the improvement of an API misuses detector’s capabilities, we performed a case study on the state-of the-art misuse detection tool CogniCrypt. The study showed that FUM can be used to properly assess CogniCrypt’s capabilities, identify weaknesses and assist in deriving mitigations and improvements.
Keywords: API misuses API usage constraints; classification framework; API misuse detection; static analysis

Approximate simulation of the hysteresis friction of radial shaft seals - Bührmann, Tobias; Magyar, Balázs (Tribologie und Schmierungstechnik)

Ergebnisse des UneS-Projektes und mögliche Handlungsempfehlungen für die Unterstützung von chancengerechten digitalisierungsbezogenen Schulentwicklungsprozessen durch Schulträger - Drossel, Kerstin; Bette, Ricarda; Oldak, Anna; Eickelmann, Birgit

Ergebnisse des UneS-Projektes und mögliche Handlungsempfehlungen für chancengerechte digitalisierungsbezogene Schulentwicklungsprozesse auf Einzelschulebene - Drossel, Kerstin; Oldak, Anna; Bette, Ricarda; Eickelmann, Birgit

Prozesskettenorientierte Herstellbarkeitsanalyse von Produkten durch die Nutzung eines Constraint-Satisfaction-Problems - Herrmann, Kevin; Pusch, Felix; Plappert, Stefan; Bode, Behrend; Mozgova, Iryna; Gembarski, Paul Christoph; Lachmayer, Roland (Stuttgarter Symposium für Produktentwicklung SSP 2023: Tagungsband zur Konferenz)
Dieser Beitrag stellt eine rechnergestützte Modellierungsstrategie vor, um Prozesskettenwissen, wie die Gestaltung der Fertigungsstufen, prozessübergreifende Fertigungsrestriktionen oder Fertigungshilfsmittel, für die Produktgestaltung zu formalisieren und im Kontext des Design for Manufacturing für Produkt- und Prozessgestaltungsentscheidungen bereitzustellen. Dabei werden am Beispiel einer Tailored-Forming-Prozesskette die Herstellungsschritte einer Multimaterial-Welle mittels eines Constraint-Satisfaction-Problems (CSP) modelliert, indem die geometrischen Transformationen einzelner Fertigungsstufen sowie Fertigungsrestriktionen in Form von Constraints und Fertigungsstufen sowie Fertigungshilfsmittel über Parameter in den CSP-Variablen formuliert werden. Das CSP ist damit in der Lage, ausgehend von einem Geometriemodell eines Bauteils eine prozesskettenorientierte Restriktionsprüfung zur Herstellbarkeitsbewertung durchzuführen und automatisiert Fertigungsstufen sowie Fertigungshilfsmittel zu konfigurieren.

ENHANCED FINDABILITY AND REUSABILITY OF ENGINEERING DATA BY CONTEXTUAL METADATA - Altun, Osman; Oladazimi, Pooya; Wawer, Max Leo; Raumel, Selina; Wurz, Marc; Barienti, Khemais; Nürnberger, Florian; Lachmayer, Roland; Mozgova, Iryna; Koepler, Oliver; Auer, Sören (Proceedings of the Design Society)
Abstract Complex research problems are increasingly addressed by interdisciplinary, collaborate research projects generating large amounts of heterogeneous amounts of data. The overarching processing, analysis and availability of data are critical success factors for these research efforts. Data repositories enable long term availability of such data for the scientific community. The findability and therefore reusability strongly builds on comprehensive annotations of datasets stored in repositories. Often generic metadata schema are used to annotate data. In this publication we describe the implementation of discipline specific metadata into a data repository to provide more contextual information about data. To avoid extra workload for researchers to provide such metadata a workflow with standardised data templates for automated metadata extraction during the ingest process has been developed. The enriched metadata are in the following used in the development of two repository plugins for data comparison and data visualisation. The added values of discipline-specific annotations and derived search features to support matching and reusable data is then demonstrated by use cases of two Collaborative Research Centres (CRC 1368 and CRC 1153).

Datenqualitätssicherung im Forschungsprozess am Beispiel von Zugversuchen - Müller, Laura; Wawer, Max Leo; Heimes, Norman; Uhe, Johanna; Koepler, Oliver; Auer, Sören; Lachmayer, Roland; Mozgova, Iryna (DS 125: Proceedings of the 34th Symposium Design for X (DFX2023))
Progressive digitization throughout the entire product data life cycle requires a more sensitive handling and understanding of data within engineering processes. Regarding engineering research data, the aim is to implement the FAIR data principles (Findable, Accessible, Interoperable, Reusable) to guarantee the post-usability of research data. To ensure the quality of data throughout the entire research process a methodical approach had been developed. Based on the quality categories Intrinsic, Representative, Contextual and Available, the related quality dimensions are considered differentiated along the research data life cycle and presented in a concept. As a use case, this concept is carried out on a tensile test with documentation of results in a research data management system.

Approach for a Safety Element out of Context for an Actuator Circuit Control Module - Noun, H.; Mozgova, Iryna; Abdelfattah, M.; Zeller, G.; Rajesh, G.; Lachmayer, R. (International Journal of Industrial and Manufacturing Engineering)
Several modules in automotive are usually modified and adapted for various project-specific applications. Due to a standardized safety concept a high reusability is accessible. A safety element out of context (SEooC) according to ISO 26262 can be a suitable approach. Based on the same safety concept and analysis, common modules can reach high reusability. For developing according to a module out of context, an appropriate and detailed development approach is required. This paper shows how to deduce this development processes for platform modules. Therefore, the detailed approach of the SEooC is derived. The aim is to create a detailed workflow for all phases of the development and integration of any kind of system modules. As an application example, an automotive project for an actuator control module is considered.

Numerical Investigation of the Coupled Friction Behavior in the Clinching Process Chain - Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Meschut, Gerson (Lecture Notes in Mechanical Engineering)

HenDi-Data (data package) v2.0.0 - Capelle, Irmlind; Minetti, Elena; Ried, Dennis; Tumat, Antje
This is the data set of the project Henze-Digital. It contains project specific authority files (e.g., persons, organizations, places) and editions (e.g., letters, documents).

HenDi-Data (data package) v1.0.0 - Capelle, Irmlind; Minetti, Elena; Ried, Dennis; Tumat, Antje
This is the data set of the project Henze-Digital. It contains project specific authority files (e.g., persons, organizations, places) and editions (e.g., letters, documents).

Ersatzmodellentwicklung zur Berücksichtigung der lokalen Fügeelementkinematik in mechanisch gefügten Verbindungen für die Bauteilauslegung im stahlintensiven Karosseriebau - Bähr, Philipp; Striewe, Marius; Meschut, Gerson; Sommer, Silke; Hein, David (13. Kolloquium: Gemeinsame Forschung in der Mechanischen Fügetechnik)

Methode zur Simulation des temperaturabhängigen Crashverhaltens von strukturellen Klebverbindungen - Striewe, Marius; Teutenberg, Dominik; Hein, David; Meschut, Gerson; Schmelzle, Lars; Mergheim, Julia; Possart, Gunnar (Klebtechnische Doktorandenseminare 2020 - 2022)

proDruck 3D-Druck – Technologie der Industrie 4.0 – als Mittel der Inklusion für Menschen mit Behinderungen in die Arbeitswelt - Kruse, Anne; Müller, Laura; Ott, Manuel; Koch, Rainer; Hügel, Joachim; Finke, Florian; Winter, Stephan; Gust, Thomas (Personennahe Dienstleistungen der Zukunft)

3D-Druck – Eine Technologie als Schlüssel zur Steigerung der Teilhabe - Kruse, Anne; Müller, Laura; Ott, Manuel; Jung, Philipp; Koch, Rainer; Hügel, Joachim; Finke, Florian; Winter, Stephan; Gust, Thomas (Personennahe Dienstleistungen der Zukunft)

When High‐Temperature Cesium Chemistry Meets Self‐Templating: Metal Acetates as Building Blocks of Unusual Highly Porous Carbons - Li, Jiaxin; Kossmann, Janina; Zeng, Ke; Zhang, Kun; Wang, Bingjie; Weinberger, Christian; Antonietti, Markus; Odziomek, Mateusz; López‐Salas, Nieves (Angewandte Chemie International Edition)
Self-templating is a facile strategy for synthesizing porous carbons by direct pyrolysis of organic metal salts. However, the method typically suffers from low yields (<4%) and limited specific surface areas (SSA<2000 m2 g−1) originating from low activity of metal cations (e.g., K+ or Na+) in promoting construction and activation of carbon frameworks. Here we use cesium acetate as the only precursor of oxo-carbons with large SSA of the order of 3000 m2 g−1, pore volume approaching 2 cm3 g−1, tunable oxygen contents, and yields of up to 15 %. We unravel the role of Cs+ as an efficient promoter of framework formation, templating and etching agent, while acetates act as carbon/oxygen sources of carbonaceous frameworks. The oxo-carbons show record-high CO2 uptake of 8.71 mmol g−1 and an ultimate specific capacitance of 313 F g−1 in the supercapacitor. This study helps to understand and rationally tailor the materials design by a still rare organic solid-state chemistry.
Keywords: CO2 Adsorption; Cesium Acetate; Cesium Effect; Porous Carbons; Supercapacitor

TPACK, DPACK, XY-Pack? Eine kritische Auseinandersetzung mit der Modellierung digitaler Inhaltskompetenzen für die berufliche Bildung - Sänger, Niklas; Jenert, Tobias (Zeitschrift für Berufs- und Wirtschaftspädagogik)
Das TPACK-Modell wird häufig zur Konzeptualisierung digitaler Kompetenzen in der Lehrer:innenbildung herangezogen. Es stellt die Bezüge des Lehrer:innenwissens zwischen den Dimensionen des inhaltlichen, pädagogischen und technologischen Wissens her. Wir analysieren in diesem Beitrag die Passung von TPACK zur Modellierung digitaler Kompetenzen für den Kontext der beruflichen Bildung, insb. mit Blick auf die Inhaltsdimension. Wir argumentieren, dass TPACK und solche Modelle, die sich daran anlehnen, den doppelten inhaltlichen Gegenstandsbezug der beruflichen Bildung nicht hinreichend abbilden. Darauf aufbauend diskutieren wir mögliche Weiterentwicklungen des Modells für die berufliche Bildung sowie dessen Bedeutung für die berufliche Lehrer:innenbildung.

Evidenzbasierte Hochschuldidaktik - Scharlau, Ingrid; Jenert, Tobias (Hochschuldidaktik als Wissenschaft: Disziplinäre, interdisziplinäre und transdisziplinäre Perspektiven)

TPACK, DPACK, XY-PACK? Eine kritische Auseinandersetzung mit der Modellierung digitaler Inhaltskompetenzen für die berufliche Bildung - Sänger, Niklas

Der Einsatz von didaktischen Fallstudien zur Erkundung digital transformierter Arbeits- und Geschäftsprozesse im Studienfach Wirtschaftswissenschaft für das Lehramt an Berufskollegs - Sänger, Niklas

Didaktische Fallstudien zur exemplarischen Erkundung der digitalen Transformation der Arbeits- und Geschäftsprozesse im Studienfach Wirtschaftswissenschaft für das Lehramt an Berufskollegs - Sänger, Niklas

Technological Pedagogical Content Framework for the Vocational Teacher Education in Germany - Sänger, Niklas

Vorstellung eines Trainings zur Förderung des selbstregulierten unternehmerischen Lernens in der Entrepreneurship-Education. - Büker, Ronja; Jenert, Tobias; Fahrbach, Manuel (Jahrestagung der Sektion Berufs- und Wirtschaftspädagogik der Deutschen Gesellschaft für Erziehungswissenschaft)